Numerical Simulation of Ferrofluid Flow in Heterogeneous and Fractured Porous Media Based on Finite Element Method - Huang, Tao; Liao, Xin; Huang, Zhaoqin; Wang, Renyi (Frontiers in Earth Science, 2021)
Ferrofluid is a kind of magnetic fluid, the flow of which is controlled by an external magnetic field. Owing to this property, ferrofluid, as a new function material, has raised extensive concern in the oil industry. In this paper, the issue of ferrofluid flow in complex porous media has been studied by numerical simulation, and the validity and accuracy of the numerical algorithm are demonstrated through a 1-D horizontal tube example. Later, the effects of the magnetic force on ferrofluid flow in complex porous media, such as heterogeneous and fractured porous media, are investigated. The results show that there is basically no flow in low permeability or secondary fracture without a magnetic field, due to the characteristics of porous media and displacement pressure distribution. However, the ferrofluid flow velocity and domain can be changed by applying an external magnetic field. This novel phenomenon may provide a new idea to enhance oil recovery based on controllable flooding technology or meet other industrial needs by using ferrofluid.